The Ageing Brain: Molecular and Cellular Basis of Neurodegeneration - Azam, Shofiul; Haque, Md. Ezazul; Balakrishnan, Rengasamy; Kim, In-Su; Choi, Dong-Kug (Frontiers in Cell and Developmental Biology, 2021)
Ageing is an inevitable event in the lifecycle of all organisms, characterised by progressive physiological deterioration and increased vulnerability to death. Ageing has also been described as the primary risk factor of most neurodegenerative diseases, including Alzheimer’s disease (AD), Parkinson’s disease (PD), Huntington’s disease (HD), and frontotemporal lobar dementia (FTD). These neurodegenerative diseases occur more prevalently in the aged populations. Few effective treatments have been identified to treat these epidemic neurological crises. Neurodegenerative diseases are associated with enormous socioeconomic and personal costs. Here, the pathogenesis of AD, PD, and other neurodegenerative diseases has been presented, including a summary of their known associations with the biological hallmarks of ageing: genomic instability, telomere attrition, epigenetic alterations, loss of proteostasis, mitochondrial dysfunction, cellular senescence, deregulated nutrient sensing, stem cell exhaustion, and altered intercellular communications. Understanding the central biological mechanisms that underlie ageing is important for identifying novel therapeutic targets for neurodegenerative diseases. Potential therapeutic strategies, including the use of NAD+ precursors, mitophagy inducers, and inhibitors of cellular senescence, has also been discussed.